A importância da família na educação do ser social em interface com o ensino religioso - Rocha, Silvia Natali (2011)
This study aims to study the formation of bonds between the family as a multiple institution and religion as performative instance to the Religious Education, analyzing the importance of family in contemporary society and its crises. Under a critical bias, look at the dynamics considered "postmodern" that have emerged in the development process not only technological but also social processes which has been guided by ethics post-moralist , that extols the personal desires more than solidarity and commitment to the collective. Thus, we understand that education, par excellence, should carry at its core an feature essentially speculative, in other words, it must born with the human capacity to discuss and speculate about the world and about herself. Such education is born, so the dialogue, i.e. through reflection, with discussion to ask, finally, with the association of people motivated by common interest in research. Thus, the Religious Education should be made plural and critical of their own human religiosity in order to be relevant as a contribution to society.